The uses and gratifications of using Facebook music listening applications - Krause, Amanda; North, Adrian; Heritage, Brody (Elsevier, 2014)
Despite rapid adoption of social media as a means of music listening, little is known about users’ motivations. This study applies the uses and gratifications approach to users’ motivations for using music listening applications on Facebook. Participants completed an online survey, and 153 out of 576 respondents indicated that they used a Facebook music listening application. A principal axis factor analysis identified three different motivations for this usage, namely entertainment, communication, and habitual diversion gratifications. The entertainment and communication gratifications replicate those found in prior uses and gratifications research concerning other social networking features, illustrating the strong similarity between uses of music and social media. However, the habitual diversion gratification may serve to distinguish listening applications from other features. Identifying and explaining these factors is relevant to social media users, musicians and application designers, as they explain what motivates a means of music listening that is gaining prominence.